Вплив етнічного фактору на формування програм і діяльність політичних партій в Україні в 1917 - 1920 рр. - Куртяк, В. (Народна творчість та етнографія, 2005)
The overlook of the various political movements in Ukraine during and immediately after the revolution testify that political parties in Ukraine in 1917-1920 were divided into two opposite camps. First was created of parties for which Ukrainian liberation and the build of the new Ukrainian state is the main goal of their political struggle. For other group national interests were taken in the context of the "general Russian interests". This article gives the systematic analyses of the activity and documents of all of the present on the territory of Ukraine at the time political movements and describes them in the context of Ukrainian national interests.